The Effectiveness of The Implementation of The Independent Curriculum Based on TPACK on The Conceptual Understanding of High School Students on Momentum and Impulse Material - Anandhita, Yuhyi; Mardiana, Nana; Syahwin, Syahwin; Rizaldi, Rachmat; Fitriana, Sheila (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2025)
This study explores the implementation of Merdeka Curriculum through the Technological Pedagogical and Content Knowledge (TPACK) approach to improve senior high school students' conceptual understanding of momentum and impulse. Merdeka Curriculum emphasizes innovative and flexible learning, but its practical application in improving students' conceptual knowledge, especially in physics, remains unexplored. thus highlighting the need for teaching strategies that integrate technology, pedagogy, and content effectively. This research was conducted at SMA Nurul Iman Tanjung Morawa with class XI MIA 1 as the experimental group and XI MIA 2 as the control group. A quasi-experimental design with non-equivalent control groups was used, where the experimental group received instruction using the TPACK approach, while the control group followed conventional teaching methods. Data analysis using SPSS version 25 showed that the experimental group achieved a mean score of 71.42 (71%), compared to 62.29 (62%) for the control group. These results indicate that the implementation of TPACK-based curriculum is effective in improving students' conceptual understanding. Statistical analysis yielded a significance value of 0.037 (<0.05), which confirmed the success of the approach. Thus, this study concludes that the implementation of the TPACK-based Merdeka Curriculum effectively improves senior high school students' conceptual understanding of momentum and impulse.